Anti Tuberculosis Therapy Combined with Oral Corticosteroid and Intra Vitreal Anti-VEGF in Ocular Tuberculosis - Ira Aldita; Junaedi Sirajuddin; Sitti Soraya Taufik; A Muhammad Ichsan (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2020)
Objective : To report a late diagnosed case of posterior uveitis tuberculosis and to create awareness to ophthalmologists for treating ocular tuberculosis as soon as possible. Case Presentation : A 17-year old woman with a complaint of decreased vision in both eyes for the past 5 days. She had a history of non-purulent cough. In the initial examination, the patient was diagnosed and treated with papil edema and chorioretinitis with sub-retinal abscess and swollen disc, but she did not show any improvement. The patient was referred to the other ophthalmologist and diagnosed with ocular and systemic tuberculosis infection with choroidal neovascularization. The infection in the macula affected and aggravated visual acuity of counting finger at 1 meters. Anti-tuberculosis, oral corticosteroid and intravitreal anti-VEGF therapy were performed. The treatment showed significant improvement toward visual outcome and retinal condition. Conclusion : Treatment with oral corticosteroid treatment along the systemic tuberculosis medication and intravitreal anti-VEGF showed good outcome on the right eye but deteriorated on the fellow eye.